Financiamento à inovação em Biotecnologia: uma avaliação da atuação da FINEP no aporte de recursos não-reembolsáveis - Renan Gadoni Canaan (2016)
Risks and uncertainties inherent to the innovation process in Biotechnology call upon specific funding instruments from government in order to share risks with the private sector. As the non-refundable contributions are a very relevant innovation funding instrument, it is necessary to understand how these investments are being made. The aim of the present study was to evaluate, through descriptive research, the profile of non-refundable contributions made by FINEP in Biotechnology in the period 2007-2014. This research indicates that R$ 355 million were invested in biotechnology in 196 different projects, corresponding to 20% of total non-refundable contributions executed by FINEP. The Human Health sector was the most contemplated, indicating that as the most preponderant sector among Brazilian biotechnology companies, it seems to be the most able to raise non-refundable contributions from FINEP. The state of São Paulo, whose configuration and infrastructure are appropriate to propose and raise funds for innovation projects, appears as the federal unit that received more contributions in biotechnology. In total, 138 companies raised non-refundable contributions in biotechnology from FINEP, and 34 more than once. These non-refundable contributions may have been essential in changing technological route of some companies, shifting to the technological paradigm of biotechnology. Among biotechnology application sectors, Human Health showed higher uncertainty, due to additional uncertainty caused by licensing procedures. Among Biotechnology techniques, nanobiotechnology showed the greatest average technology uncertainty, once its placed at the intersection of two highly innovative areas: nanotechnology and biotechnology. This high uncertainty in nanobiotechnology evidences its place at the frontier of knowledge.